2017
DOI: 10.1002/aet2.10014
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Variations in Emergency Medicine Residency Training of Ultrasound‐guided Regional Anesthesia Techniques

Abstract: Background: Ultrasound guidance has become an integral component to procedural and diagnostic practice for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Wilson et al . report that most emergency ultrasound departments have no interdisciplinary collaborations around UGRA.…”
Section: We Urgently Need Emergency Physicians To Specialize In Pain mentioning
confidence: 99%
See 4 more Smart Citations
“…Wilson et al . report that most emergency ultrasound departments have no interdisciplinary collaborations around UGRA.…”
Section: We Urgently Need Emergency Physicians To Specialize In Pain mentioning
confidence: 99%
“…We need to look no further than our early and enthusiastic embrace of point‐of‐care ultrasound and free open‐access medical education (FOAMed) as examples. However, Wilson et al . found that despite the clear recognition that UGRA is an important skill, nearly 30% of programs offer no training in UGRA to their residents or fellows.…”
mentioning
confidence: 98%
See 3 more Smart Citations